2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00552
|View full text |Cite
|
Sign up to set email alerts
|

LaSOT: A High-Quality Benchmark for Large-Scale Single Object Tracking

Abstract: In this paper, we present LaSOT, a high-quality benchmark for Large-scale Single Object Tracking. LaSOT consists of 1,400 sequences with more than 3.5M frames in total. Each frame in these sequences is carefully and manually annotated with a bounding box, making LaSOT the largest, to the best of our knowledge, densely annotated tracking benchmark. The average video length of LaSOT is more than 2,500 frames, and each sequence comprises various challenges deriving from the wild where target objects may disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
269
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,015 publications
(368 citation statements)
references
References 91 publications
(334 reference statements)
2
269
0
Order By: Relevance
“…The proposed network was then trained inside an RL on-policy asynchronous Actor-Critic framework [32] that incorporated parallel SL agents. Experiments showed that the proposed A3CT and A3CTD trackers outperform state-of-theart methods on the most recent the GOT-10k test set [18], LaSOT [9], UAV123 [35] benchmarks, and perform comparably with the state-of-the-art on OTB-2015 [50] and VOT benchmarks [26]. Moreover, A3CT and A3CTD achieved a processing speed of 90 and 50 FPS respectively and thus are suitable for real-time applications.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The proposed network was then trained inside an RL on-policy asynchronous Actor-Critic framework [32] that incorporated parallel SL agents. Experiments showed that the proposed A3CT and A3CTD trackers outperform state-of-theart methods on the most recent the GOT-10k test set [18], LaSOT [9], UAV123 [35] benchmarks, and perform comparably with the state-of-the-art on OTB-2015 [50] and VOT benchmarks [26]. Moreover, A3CT and A3CTD achieved a processing speed of 90 and 50 FPS respectively and thus are suitable for real-time applications.…”
Section: Discussionmentioning
confidence: 93%
“…In this section we report the experimental setup and we discuss the results, obtained by the proposed trackers A3CT and A3CTD, on the benchmarks GOT-10k [18], LaSOT [9], UAV123 [35], OTB-100 [50], VOT-2018 [26] and VOT-2019.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations